Estudo de matérias-primas fundentes alternativas ao feldspato na fabricação de produtos cerâmicos - Souza, Tayná Cunha (2020)
Brazil is one of the world's leading producers and consumers of ceramic tiles. Among ceramic tiles, porcelain tiles are gaining prominence due to their technical and aesthetic characteristics. However, its trade price is one of the limiting factors to its choice and use. This price is related to production costs, of which the cost of raw materials stands out and, among these, feldspars, the main melting raw material used in the formulation of porcelain tiles, have higher values. In Brazil, this mineral is obtained mainly from pegmatitic reserves located in the Northeast and in the North of Minas Gerais. However, most companies in the ceramic segment are located in the south and southeast regions of the country (especially in the states of São Paulo and Santa Catarina), resulting in high freight costs, which reflects in the final product costs. Thus, this research aimed at the study of alternative melting raw materials and located close to the ceramic production pole that enable the manufacture of products that meet the parameters specified in the ABNT NBR-15463: 2013 standard and with a relative reduction in final costs. For this purpose, samples of potassic rocks (nepheline syenites) from mining waste piles in the regions of Caldas (Rocha C.) and Poços de Caldas/MG (Rocha P.C.) were used, as well as processed and commercial raw materials (K-feldspar and Nepheline syenite), in the preparation of 7 formulations (F1 - 100% K-Feldspar; F2 - 75% K-Feldspar and 25% Rocha C.; F3 - 50% K-Feldspar and 50% Rocha C.; F4 - 25% K-Feldspar and 75% Rocha C.; F5 - 100% Rocha C.; F6 - 100% Rocha P.C. and F7 - 100% Nepheline syenite standard), in order to obtain porcelain tiles. Specimens prepared with these formulations were subjected to firing at variable temperatures (1100°C to 1320°C) and, subsequently, characterized for their ceramic properties. The results showed that Rocha C. has a high melting character, making it possible to obtain products that meet the normative parameters with a significant reduction in the firing temperature up to 1180°C. Rocha PC, although having a high melting character, was not shown to be viable for the production of commercial porcelain tiles, for the adopted formulation, due to the need to use a sintering temperature higher than that commonly used in the production of porcelain tiles (1300°C), implying in the increased energy expenditure. The benefited Nefelina syenite made it possible to obtain the products from fires at 1240°C, with characteristics similar to commercial porcelain tiles and lighter coloration, when compared to the other alternative raw materials evaluated.